Perceptions of the managers of a university hospital about quality in health - Sâmia Jamylle Santos de Azevedo; Larissa Kelly Silva de Moura; Camila Matias Nascimento; Theo Duarte da Costa; Pétala Tuani Candido de Oliveira Salvador (Universidade Federal de Santa Maria, 2020)
Objective: to describe the perceptions of managers of a university hospital about quality in health. Method: this is a descriptive study, with a qualitative approach, carried out in a university hospital in Northeast Brazil. The study population was composed of 60 managers. Data were collected between 2017 and 2018, based on a semi-structured interview. Lexicographic textual analysis was performed with the support of the IRaMuTeQ software. Results: 593 text segments were analyzed and classified in the following categories: "Influence of the management model", "Quality management tools", "Conceptions of quality in health" and "Health promotion actions". The managers understood that the management model adopted influences care, and, consequently, its quality. Conclusion: it was found that managers related quality to the problem-solving service provided to users, as well as to a good relationship between professionals and the consequent improvement in the work process.